Injúria foliar em diferentes estágios fenológicos de plantas de girassol e seu efeito na produção - Lucas, Dioneia Daiane Pitol (2011)
The sustainability of the crop production, i.e. the ability to remain itself in the market, protecting the environment and have good financial returns is often threatened by risk factors. Among the risk factors in agriculture, highlights the climatic factor, and hail occurrence of extreme events of this factor. The objective of this study was to evaluate sunflower plants responses after application of different levels of injury in leaves in different phenological stages, to quantify the injury effect on the productivity reduction of achenes. In addition, mathematical models were developed to estimate the production reduction in function of crop development stage and occurrence intensity of injury in leaves. The experiments were conducted at Crop Science Department of the Federal University of Santa Maria, Santa Maria, RS, Brazil, in the agricultural years 2009/2010 and 2010/2011, following the growth and development of plants during the crop cycle through phenological and phenometric observations. The meteorological data were obtained from the meteorological station of Santa Maria, belonging to 8th DISME/INMET/MA. Were made sixteen treatments arranged in a randomized block design with three replications for the 2009/2010 agricultural year and fifteen treatments for the 2010/2011 agricultural year. The treatments consisted of four foliar injury levels (0, 25, 50 and 75%) applied at four phenological stages (20 emitted leaves, R2, R5.1 and R6) of sunflower plants in the experiment conducted in 2009/2010 and five foliar injury levels (0, 25, 50, 75 and 100%) applied at three phenological stages (20 emitted leaves, R2 and R6) of sunflower plants in 2010/2011. The injuries were promoted by perforations in leaf blade of all sunflower leaves with auger of 23, 25 and 30 mm in diameter. The number of perforations was set according of leaves width, auger diameter and desired injury level. The sunflower yield was affected by injury levels applied and by stages considered. The reproductive stage R2 was most affected by injuries, while 25% injury level had caused proportionally greater effect on sunflower yield.